(untitled) (Annals of Medical Research, 2021)
Aim: Bile duct repair surgery in injured patients is delayed in general until the inflammation is resolved. In this study we aimed to investigate whether early repair yields good results in bile duct injuries.Material and Methods: A total of 62 patients with the diagnosis of bile duct injury and treated in our hospital between March 2016 and November 2018 were included in the study. In all patients, ERCP was performed for identification of the type and severity of the injury. The type and severity of the injury were classified using the Strasberg classification. 32 (51.6%) of 62 patients were treated by ERCP + Stenting while the remaining 30 (48.4%) patients underwent surgery at the early period.Results: Amongst 30 patients who had undergone surgery, only one patient needed additional intervention due to leakage at the early period. The rate of anastomotic stricture and recurrent cholangitis, which are among long-term complications, was 3.3%. Conclusion: The collaboration of hepatobiliary surgeons, gastroenterologists, and interventional radiologists having skills and experience on this are very important. Early repair can yield good result in experienced centers.